Proactive Personality And Transformational Leadership As Drivers Of Innovative Work Behavior: The Mediating Role Of Work Engagement In The Public Sector - Meyfrina Kristiana Tarigan; Aryana Satrya (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study examines the effects of proactive personality and transformational leadership on innovative work behavior, with work engagement as a mediating variable among civil servants in a public-sector institution responsible for market regulation and service delivery. Using a quantitative cross-sectional design, data were obtained from 331 employees and analyzed with PLS-SEM. The results show that all hypotheses were supported. Proactive personality was the strongest predictor of both innovative work behavior and work engagement, while transformational leadership also positively influenced innovative work behavior directly and indirectly through engagement. Work engagement significantly mediated the effects of both predictors on innovative behavior. These findings highlight that innovation in the public sector is driven by individual readiness and leadership quality. Strengthening proactive traits and implementing transformational leadership are therefore crucial for fostering an innovation-oriented culture. The study further contributes theoretically by identifying work engagement as a key psychological mechanism linking personal and contextual factors to innovative behavior.